2018
DOI: 10.1093/humupd/dmy032
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to non-persistent chemicals in consumer products and fecundability: a systematic review

Abstract: Exposure to non-persistent chemicals in consumer products is ubiquitous and associated with endocrine-disrupting effects. These effects have been linked to infertility and adverse pregnancy outcomes in some studies and could affect couple fecundability, i.e. the capacity to conceive a pregnancy, quantified as time to pregnancy (TTP).OBJECTIVE AND RATIONALE: Few epidemiologic studies have examined the impact of non-persistent chemicals specifically on TTP, and the results of these studies have not been synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 163 publications
(192 reference statements)
1
51
0
Order By: Relevance
“…As the study of Garlantézec et al . is the only study that showed such results, Hipwell et al . concluded in their review that it was not possible to draw a final conclusion without additional data.…”
Section: Review Of Safety Datamentioning
confidence: 96%
See 3 more Smart Citations
“…As the study of Garlantézec et al . is the only study that showed such results, Hipwell et al . concluded in their review that it was not possible to draw a final conclusion without additional data.…”
Section: Review Of Safety Datamentioning
confidence: 96%
“…However, the June 2015 high‐throughput Endocrine Disruptor Screening Program conducted by the US‐EPA determined that phenoxyethanol has no oestrogenic activity . Moreover, a systematic review has been recently published studying the association between exposure to non‐persistent chemicals in consumer products and fecundability . Amongst the 12 studies included in this review, only one observational study conducted by Garlantézec et al .…”
Section: Review Of Safety Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Fecundability, as measured by time to pregnancy (TTP), is used as a sensitive reproductive outcome appropriate for studying the impact of environmental exposures. Decreased fecundability has been associated with life style exposures including tobacco, alcohol, and obesity; occupational exposures including pesticides; and environmental chemicals in consumer products . Longer TTP has been associated with adverse pregnancy outcomes including miscarriage, preterm birth, and low birthweight as well as reports of increased adverse outcomes in the neonate and child development .…”
Section: Introductionmentioning
confidence: 99%